Potential Human Models of Infammatory Bowel Disease - Stephen B Hanauer (Canadian Journal of Gastroenterology)
Similar to animal models of inflammatory bowel disease (IBD), there is no single human model representative of ulcerative colitis or Crohn's disease. An optimal human model awaits etiopathogenetic definitions and further reclassification or depiction of clinicopathological scenarios. Current human models can be classified into models depicting risk of disease; preclinical disease; acute inflammation; and miscellaneous IBD. Family studies are the best means of pursuing patients at risk. Evolving genetic and serological markers may further identify subgroups to assess with permeability probes, leukocyte scans or endoscopy for preclinical disease. Provocation with nonsteroidal anti-inflammatory drugs (NSAIDs) may be useful in selected patients because NSAID mucosal damage may induce or mimic IBD. Alternative natural history or interventional studies in patients with human leukocyte antigen (HLA)-B27 spondylarthropathy may be useful. The disease margin and pouchitis are models within the disease state of ulcerative colitis as are the aphthous ulcer, anastomotic margin and diverted fecal stream for Crohn's disease. Newly defined colitides, such as microscopic and collagenous colitis and diversion colitis, also provide potential comparative models to evaluate mucosal immune, inflammatory, reparative, secretory and absorptive regulation.